DAMPAK INTERVENSI EDUKASI TERHADAP PENGETAHUAN, SIKAP, DAN KETERAMPILAN ORANG TUA DALAM MENGELOLA NYERI PADA ANAK DENGAN KANKER - Imelda Pujiharti; A Allenidekania; Happy Hayati (Jurnal Afiat : Kesehatan dan Anak, 2019)
Introduction pain in children suffers from cancer gives effect in short term and long term. Most parents do not know how to assess pain in children. They have not used a pain scale based on children age to measure pain. Health education pain management has not been structured for patients so the given information is not optimal. The purpose this study aims to identify the impact of education intervention to the parent’s knowledge, attitudes, and skills in managing pain of children suffers from cancer. This research method This study used a quasi-experimental with one group pretest-posttest. The sample was 29 people in RSAB Harapan Kita and Gatot Subroto Army Hospital, taken by consecutive sampling. The data was analyzed by McNemar and Chi Square. The results showed a significant difference in the aspect of knowledge, attitudes and skills of parent in the pain management of children before and after health education (knowledge, p = 0.001; Attitudes, p = 0.001 and skill, p < 0.001). The conclusion characteristics of parents associated with the knowledge and attitudes who have children suffers from cancer is pain management experience. Suggestions recommendation for this study is the health education about pain management should be carried out intensively.